Association of Musculoskeletal Pain with Poor Quality of Sleep Among E-Gamers in a Private University in Malaysia - Leong, Yi Zuang; Sumedha, .; Clements, Jim Brown (INTI International University, 2022)
Background: Electronic sports (e-sports) requires prolonged sitting and repetitive movements which makes e-gamers susceptible to develop musculoskeletal pain in different body parts. Moreover, their quality of sleep may also be affected. It is very important for physiotherapist to identify the relationship between musculoskeletal pain and poor quality of sleep among e-gamers, so as to develop more precise treatment plan and provide higher quality of patient education. Objective: The purpose of this study was to analyse the association between musculoskeletal pain with poor quality of sleep among e-gamers in a private university in Malaysia. Methodology: The sample consisted of 42 e-gamers from a private university in Malaysia. A cross-sectional study was conducted by using Nordic Musculoskeletal Questionnaire and Sleep Quality Scale. The association between musculoskeletal pain and poor sleep quality was evaluated using chi-square test. Results: The results showed that more than half of the study population reported with a higher prevalence of neck pain in the past year and in the previous week, followed by shoulders, wrists and hands. Besides, half of the participants also reported that they had very poor sleep quality (50%), followed by the category of poor quality of sleep (23.8%). E-gamers with poor sleep quality showed significant association with musculoskeletal pain in neck (p= 0.004), shoulder (p= 0.052), upper back (p=0.043), wrist and hands (p= 0.004). Conclusion: Our findings revealed that musculoskeletal pain in neck, shoulder, upper back, wrist and hands was significantly associated with poor sleep quality among e-gamers. Health promotion actions that contribute towards improvement in quality of sleep and prevention of musculoskeletal pain should be considered, so the performance and quality of life among the e-gamers could be improved.